Stiffer Spleen Predicts Higher Bone Marrow Fibrosis and Higher JAK2 Allele Burden in Patients With Myeloproliferative Neoplasms - Moia, Riccardo; Cittone, Micol Giulia; Boggione, Paola; Manfredi, Giulia Francesca; Favini, Chiara; Awikeh, Bassel; Pedrinelli, Anita Rebecca; Mahmoud, Abdurraouf Mokhtar; Nicolosi, Maura; Bellan, Mattia; Sainaghi, Pier Paolo; Pirisi, Mario; et al. (Frontiers in Oncology, 2021)
Sixty-three myeloproliferative neoplasms (MPN; 9 polycythaemia vera [PV], 32 essential thrombocythemia [ET] and 22 myelofibrosis [MF]) underwent spleen stiffness (SS) measurement by vibration-controlled transient elastography equipped with a novel spleen-dedicated module. Higher SS values significantly correlated with grade 2-3 bone marrow (BM) fibrosis (p=0.035), with haemoglobin level <10 g/dl (p=0.014) and with white blood cells >10,000/l (p=0.008). Median SS was significantly higher in MF patients compared to ET and PV (p=0.015). SS also correlated with higher JAK2 variant allele frequency (p=0.02). This study identifies SS as a potential non-invasive tool that reflects BM fibrosis and the mutational burden in MPN.